Virological failure and HIV drug resistance among adults living with HIV on second‐line antiretroviral therapy in the Asia‐Pacific. Issue 3 (5th November 2020) - Ross, J; Jiamsakul, A; Kumarasamy, N; Azwa, I; Merati, TP; Do, CD; Lee, MP; Ly, PS; Yunihastuti, E; Nguyen, KV; Ditangco, R; Ng, OT; et al.
Abstract : Objectives: To assess second‐line antiretroviral therapy (ART) virological failure and HIV drug resistance‐associated mutations (RAMs), in support of third‐line regimen planning in Asia. Methods: Adults > 18 years of age on second‐line ART for ≥ 6 months were eligible. Cross‐sectional data on HIV viral load (VL) and genotypic resistance testing were collected or testing was conducted between July 2015 and May 2017 at 12 Asia‐Pacific sites. Virological failure (VF) was defined as VL > 1000 copies/mL with a second VL > 1000 copies/mL within 3–6 months. FASTA files were submitted to Stanford University HIV Drug Resistance Database and RAMs were compared against the IAS‐USA 2019 mutations list. VF risk factors were analysed using logistic regression. Results: Of 1378 patients, 74% were male and 70% acquired HIV through heterosexual exposure. At second‐line switch, median [interquartile range (IQR)] age was 37 (32–42) years and median (IQR) CD4 count was 103 (43.5–229.5) cells/µL; 93% received regimens with boosted protease inhibitors (PIs). Median duration on second line was 3 years. Among 101 patients (7%) with VF, CD4 count > 200 cells/µL at switch [odds ratio (OR) = 0.36, 95% confidence interval (CI): 0.17–0.77 vs . CD4 ≤ 50) and HIV exposure through male–male sex (OR = 0.32, 95% CI: 0.17–0.64 vs . heterosexual) or injecting drug use (OR = 0.24, 95% CI: 0.12–0.49) were associated with reduced VF. Of 41 (41%) patients with resistance data, 80% had at least one RAM to nonnucleoside reverse transcriptase inhibitors (NNRTIs), 63% to NRTIs, and 35% to PIs. Of those with PI RAMs, 71% had two or more. Conclusions: There were low proportions with VF and significant RAMs in our cohort, reflecting the durability of current second‐line regimens.